A metabarcoding comparison of windward and leeward airborne algal diversity across the Ko'olau mountain range on the island of O'ahu, Hawai'i1. Issue 2 (31st January 2017) - Sherwood, Alison R.; Dittbern, Monica N.; Johnston, Emily T.; Conklin, Kimberly Y.
Abstract : Airborne algae from sites on the windward ( n  = 3) and leeward ( n  = 3) sides of the Ko'olau Mountain range of O'ahu, Hawai'i, were sampled for a 16 d period during January and February 2015 using passive collection devices and were characterized using Illumina MiSeq sequencing of the universal plastid amplicon marker. Amplicons were assigned to 3, 023 operational taxonomic units (OTUs), which included 1, 189 cyanobacteria, 1, 009 heterotrophic bacteria, and 304 Eukaryota (of which 284 were algae and land plants). Analyses demonstrated substantially more OTUs at windward than leeward O'ahu sites during the sampling period. Removal of nonalgal OTUs revealed a greater number of algal reads recovered from windward (839, 853) than leeward sites (355, 387), with the majority of these being cyanobacteria. The 1, 234 total algal OTUs included cyanobacteria, diatoms, cryptophytes, brown algae, chlorophyte green algae, and charophyte green algae. A total of 208 algal OTUs were identified from leeward side samplers (including OTUs in common among samplers) and 1, 995 algal OTUs were identified from windward samplers. Barcoding analyses of the most abundant algal OTUs indicated that very few were shared between the windward and leeward sides of the Ko'olau Mountains, highlighting the localized scale at which these airborne algae communities differ. Back trajectories of air masses arriving on O'ahu during the sampling period were calculated using the NOAA HY‐SPLIT model and suggested that the sampling period was composed of three large‐scale meteorological events, indicating a diversity of potential sources of airborne algae outside of the Hawaiian Islands.